PERAN GURU DALAM MENGEMBANGKAN TIGA KECERDASAN SISWA DI MIN 3 NAGAN RAYA - Asnidar, Asnidar; Mahmud, Salami (Program Studi Manajemen Pendidikan Islam, 2024)
In this era of industrial revolution 4.0, the role of teachers is very urgent in developing social intelligence, spiritual intelligence, and intellectual intelligence of students in madrasah. The purpose of this study was to determine the role of teachers in developing the three intelligences. This research uses a qualitative approach with descriptive methods. Data collection techniques through observation, interviews and document studies. While the data processing technique uses Sugiyono's theory by reducing data (data reduction), presenting data (data display), and verifying data (drawing conclusions). The results showed that the teacher as a student mentor has acted as a model and facilitator in developing students' social intelligence, both in the classroom and outside the classroom. Then the teacher as a student educator has acted as a coach in the process of habituation and exemplary examples that can be emulated in developing students' spiritual intelligence, both outwardly and spiritually. Furthermore, the teacher as a teacher has played a role in transferring various disciplines in developing the intellectual intelligence of students which is useful for their future. The results of this study can be recommended to the Head of the District / City Office of the Ministry of Religious Affairs through the Head of Madrasah to improve the professionalism of teachers who are able to apply the three intelligences of students in madrasah.